1998
DOI: 10.1074/jbc.273.10.5841
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-9, Bcl-XL, and Apaf-1 Form a Ternary Complex

Abstract: Genetic analysis of apoptosis in the nematode Caenorhabditis elegans has revealed the cell death machine to be composed of three core interacting components. CED-4 (equivalent to mammalian Apaf-1) is a nucleotide binding molecule that complexes with the zymogen form of the death protease CED-3, leading to its autoactivation and cell death. CED-9 blocks death by complexing with CED-4 and attenuating its ability to promote CED-3 activation. An equivalent ternary complex was found to be present in mammalian cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
313
4
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(337 citation statements)
references
References 32 publications
18
313
4
2
Order By: Relevance
“…The ®nding that Bax induces caspase-independent cell death is in agreement with previous reports (Xiang et al, 1996;Pastorino et al, 1998;Gross et al, 1998), although other studies show that the Bax-induced cell death requires caspase activity (Pan et al, 1998;Martinou et al, 1998;Finucane et al, 1999;Cheng et al, 1997). This discrepancy may be attributable to the fact that Bax can induce both caspase-dependent and caspase-independent pathways and that the pathway employed may depend on the nature of the cells which express it.…”
Section: Bax and Bcl-x S Induce Different Cell Death Pathways In Pc12supporting
confidence: 92%
“…The ®nding that Bax induces caspase-independent cell death is in agreement with previous reports (Xiang et al, 1996;Pastorino et al, 1998;Gross et al, 1998), although other studies show that the Bax-induced cell death requires caspase activity (Pan et al, 1998;Martinou et al, 1998;Finucane et al, 1999;Cheng et al, 1997). This discrepancy may be attributable to the fact that Bax can induce both caspase-dependent and caspase-independent pathways and that the pathway employed may depend on the nature of the cells which express it.…”
Section: Bax and Bcl-x S Induce Different Cell Death Pathways In Pc12supporting
confidence: 92%
“…[49][50][51] When overexpressed, this mutant functions as a dominant negative (DN) inhibiting caspase 9-mediated apoptosis in vivo, 9 although it does not inhibit the activity of recombinant caspase 9 in vitro. 52 Stable transfected cells were selected with neomycin and several individual clones were isolated that expressed Flag-tagged C9DN (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, cells were also stimulated with anti-Fas antibody. Although Fas signals induce apoptosis via the extrinsic pathway, 53 inhibition of Fas-induced cell death by C9DN has been described in MCF-7 cells, 50 although another study showed that C9DN mutant did not protect Jurkat cells from Fas-mediated apoptosis. 54 We observed that the amount of DEVDase activity induced by anti-Fas was considerably lower in Jurkat-C9DN cells than in control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian Apaf-1 includes in its C-terminal domain a set of WD40 repeats which may regulate the ability to activate caspase-9 . Consistent with the C. elegans blueprint, Bcl-X L can form a ternary complex with Apaf-1 and caspase-9 (Pan et al, 1998). Additional Bcl-2 family proteins have been identi®ed that interact directly with Apaf-1, termed Diva and Boo.…”
Section: C-myc Structure and Functionmentioning
confidence: 88%